2018
DOI: 10.1371/journal.pone.0208067
|View full text |Cite
|
Sign up to set email alerts
|

Sulfated archaeol glycolipids: Comparison with other immunological adjuvants in mice

Abstract: Archaeosomes are liposomes traditionally comprised of total polar lipids (TPL) or semi-synthetic glycerolipids of ether-linked isoprenoid phytanyl cores with varied glyco- and amino-head groups. As adjuvants, they induce robust, long-lasting humoral and cell-mediated immune responses and enhance protection in murine models of infectious disease and cancer. Traditional total polar lipid (TPL) archaeosome formulations are relatively complex and first generation semi-synthetic archaeosomes involve many synthetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 51 publications
(58 reference statements)
1
45
0
Order By: Relevance
“…While it was initially thought that entrapment of antigen within the archaeosome vesicle would enhance cytotoxic CD8 + T cell responses by delivering the antigen to the cytosol, allowing it to readily access MHC class I processing machinery that is necessary to initiate CD8 + T cell responses, these findings indicate that the inherent adjuvant effect of archaeosomes is sufficient to initiate CD8 + T cell responses towards exogenous antigens. Notably, our findings that an SLA admix archaeosome formulation functions similarly to an entrapped antigen archaeosome formulation are not out of place in the current vaccine adjuvant landscape as many other adjuvants, such as CpG or Poly (I:C), are capable of initiating CD8 + T cell responses towards exogenous antigen [10].…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…While it was initially thought that entrapment of antigen within the archaeosome vesicle would enhance cytotoxic CD8 + T cell responses by delivering the antigen to the cytosol, allowing it to readily access MHC class I processing machinery that is necessary to initiate CD8 + T cell responses, these findings indicate that the inherent adjuvant effect of archaeosomes is sufficient to initiate CD8 + T cell responses towards exogenous antigens. Notably, our findings that an SLA admix archaeosome formulation functions similarly to an entrapped antigen archaeosome formulation are not out of place in the current vaccine adjuvant landscape as many other adjuvants, such as CpG or Poly (I:C), are capable of initiating CD8 + T cell responses towards exogenous antigen [10].…”
Section: Discussionmentioning
confidence: 83%
“…In multiple pre-clinical studies, they have been shown to activate antigen-specific CD8 + T cell responses [15,19,26,27] and generate protective immunity in tumor models, e.g., B16-OVA melanoma [7,13,19,23,26,27], and against multiple infectious diseases, e.g., H1N1 influenza [11], Listeria monocytogenes [7,12], Trypanosoma cruzi [13] and Mycobacterium tuberculosis [14]. When compared to commonly used commercial adjuvants, such as Poly(I:C) or Montanide, archaeal lipid vaccines were found to elicit equal or greater antigen specific CD8 + T cell-mediated cytotoxicity and IgG responses [10]. SLA-based archaeosomes can also induce local cytokine production at the site of injection even in the absence of an antigen [19].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations